Stakeholders' Pressure on the Intention to Implement Green Budgeting - Kedisan, Anak Agung Vidyaswari; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 34 No 1 (2024), 2024)
This study examines the influence of stakeholders' pressure on the intention to implement green budgeting. The primary data were collected through surveys using a questionnaire of 5-point likert scale. The respondents are 117 department heads of star-rated hotels in Badung Regency of Bali. Using multiple linear regression, the result shows that investor pressure, visitor pressure, and environmental observer pressure have positive influence on the intention to implement green budgeting in Badung Regency star-rated hotels. This research supports the development of the theory of planned behavior, especially that subjective norms affect the existence of an intention. Keywords: Investors' Pressures; Visitors' Pressure; Environmental Observers Pressures; Intention To Implement Green Budgeting.